Cultura popular, oralidad y literatura en «Los funerales de la Mamá Grande» - Castaño Restrepo, Germán (Anales de Literatura Hispanoamericana, 2008)
In 1962 García Márquez published a story that marked the beginning of his most representative literary period. That text clarifies the cultural basis of what boom’s critics have called «Latin American literature’s magical realism». «Big Mama’s funeral» brings to literature the traditional culture’s vision of the world. It is a coup de grâce to the old fashioned speech prevailing in colombian literature, and it leads to a new literary language which is closely linked to orality.